1999
DOI: 10.1101/gad.13.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Transient gene asymmetry during sporulation and establishment of cell specificity in Bacillus subtilis

Abstract: Sporulation in Bacillus subtilis is initiated by an asymmetric division generating two cells of different size and fate. During a short interval, the smaller forespore harbors only 30% of the chromosome until the remaining part is translocated across the septum. We demonstrate that moving the gene for F , the forespore-specific transcription factor, in the trapped region of the chromosome is sufficient to produce spores in the absence of the essential activators SpoIIAA and SpoIIE. We propose that transient ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 27 publications
1
74
2
Order By: Relevance
“…3). This arrangement of genes supported a modest level of sporulation even in the absence of the normally essential factors SpoIIAA and SpoIIE (84). These results clearly suggested that transient genetic asymmetry could play a role in compartmentalization of F activity.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 49%
See 3 more Smart Citations
“…3). This arrangement of genes supported a modest level of sporulation even in the absence of the normally essential factors SpoIIAA and SpoIIE (84). These results clearly suggested that transient genetic asymmetry could play a role in compartmentalization of F activity.…”
Section: Mechanisms Of Compartmentalizationmentioning
confidence: 49%
“…As a consequence, the two cells are now genetically asymmetric. This asymmetry has important implications for compartmentalization of gene expression (54,84), as discussed below. The developing organism also has a major challenge in that it must ensure that the prespore compartment receives a complete chromosome The transfer of the origin-distal two-thirds of a chromosome from the mother cell into the prespore is concomitant with the activation of different transcription factors in the prespore and mother cell.…”
Section: Transfer Of Dna Into the Presporementioning
confidence: 99%
See 2 more Smart Citations
“…The discovery that SpoIIE localizes to the polar septum revealed a direct connection between the activation of F and the process of asymmetric division, but left unanswered the questions of how the timing and cell selectivity of F activation are determined (Frandsen et al 1999;Losick and Dworkin 1999). One possibility is that SpoIIE is displayed on both faces of the polar septum but because the forespore is much smaller than the mother cell, the ratio of phosphatase (SpoIIE) to kinase (SpoIIAB) would be substantially higher in the forespore than in the mother cell ( Fig.…”
mentioning
confidence: 99%